APPLICATION OF THE COMPACT SPECKL INTERFEROMETER FOR FLAW DETECTION - Z.T. Azamatov , V. A. Kim , N.N. Bazarbayev , B.R.Sobirov , T.Z. Azamatov , Z.F. Turdiev (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The basic principles of digital shearography or shear speckle interferometry and examples of the application of modern methods of digital shearography are considered. Experiments on obtaining shearograms with various configurations of optical elements using a Fresnel biprism and a Michelson interferometer have been carried out. Two variants of the optical scheme for forming the image shift have been tested. A scheme of a compact speckle interferometer for digital shearography based on a Michelson interferometer is proposed and implemented. A software algorithm for obtaining shearograms has been implemented. The device was tested under conditions of sensitivity to out-of-plane deformation on samples of the type of a round thin membrane. Experiments were carried out to detect defects in structures and welds by the presence of zones with non-uniform deformation